A new littoral interstitial species of the genus Isotomodes (Collembola, Isotomidae) from Italy - Fanciulli, Pietro Paolo; Dallai, Romano; Meneguz, Marco (Zootaxa, 2015)
The genus Isotomodes Linnaniemi, 1907 can be easily recognized among Isotomidae because of its remarkable morphology and chaetotaxy of the last abdominal segments (Gama, 1963; Potapov, 2001); it comprises 34 worldwide species (Bellinger et al. 2014, Potapov 2001, Arbea 2006, Abrantes & Mendonça 2007, Thibaud 2008) mainly distributed in Europe (especially in Mediterranean region) and America, and only a few from est Asia and Oceania (Bellinger et al. 2014). The genus Isotomodes appears well represented in interstitial sandy habitat, especially in supralittoral and inland biotopes, as reported by Thibaud & Christian (1997) and Thibaud (2007). The littoral fauna of Collembola along the Italian peninsula has been poorly studied (Dallai et al. 2010), so we decided to fill this gap beginning with a collecting design along the Thirrenian coast of Tuscany. As preliminary result, herein we describe a new species of Isotomodes that had been collected in the sand dune in front of the Regional Park of S. Rossore (Tuscany).